Drug metabolism and antibiotic resistance in micro‐organisms - Sim, Edith (Br J Pharmacol, 2017)
This article is part of a themed section on Drug Metabolism and Antibiotic Resistance in Micro‐organisms. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.14/issuetoc